Pengelolaan Limbah B3 Di Rumah Sakit X Kota Batam - Salma Savira Siddik; Eka Wardhani (Jurnal Serambi Engineering, 2020)
Hospital X was class b private hospitals that are located in Batam with 297 unit beds. The waste that can be categorized as solid waste medical in the hospital which is infectious, pharmacy, hazardous and toxic waste, cytotoxic, sharp object.  The purpose of this research is to identify, a source of , the characteristics, solid waste medical produced by hospital X in Batam and also conduct an evaluation of solid waste medical management hospital in accordance with the minister of environment and forestry 56 2015 on procedures and technical requirements of hazardous and toxic waste management than health service facilities. This research used primary and secondary data collection method. The research results show solid waste medical management at the hospital X in Batam most of them are in according to rule. But there are some things that must be improved are blinding trash bag, efficiency and minimal temparature the combustion chamber incinerator. Management efforts must to do are briefing to officer of the waste collection about the way to blinding trash bag in according to the regulation and the incinerator that can serve confirming to standard of burning hazardous and toxic waste.